79.1k views
2 votes
4-(2y-1)=2(5y+9)+y please help quick

User Yan Zhou
by
6.3k points

2 Answers

2 votes

Here, this is a linear equation in one variable because only one variable is there, y. We need to find the solution i.e the value of y.

Given, equation:


4 - (2y - 1) = 2(5y + 9) + y

We need to find y, So let's isolate y in any one side of the equation. Before that, let's open the parentheses.


4 - 2y + 1 = 10y + 18 + y


5 - 2y = 11y + 18

Now, let's add 2y to both sides, So that -2y on the left hand side gets cancel.


5 - 2y + 2y = 11y + 18 + 2y


5 = 13y + 18

Flipping the equation for easy calculation,


13y + 18 = 5

Solving further,


13y = - 13


y = ( - 13)/(13)


\boxed{y = - 1}

Hence, we are done !!

━━━━━━━━━━━━━━━━━━━━

User StephenLembert
by
6.1k points
4 votes

Step-by-step explanation:Step 1: Simplify both sides of the equation.

4−(2y−1)=2(5y+9)+y

4+−1(2y−1)=2(5y+9)+y(Distribute the Negative Sign)

4+−1(2y)+(−1)(−1)=2(5y+9)+y

4+−2y+1=2(5y+9)+y

4+−2y+1=(2)(5y)+(2)(9)+y(Distribute)

4+−2y+1=10y+18+y

(−2y)+(4+1)=(10y+y)+(18)(Combine Like Terms)

−2y+5=11y+18

−2y+5=11y+18

Step 2: Subtract 11y from both sides.

−2y+5−11y=11y+18−11y

−13y+5=18

Step 3: Subtract 5 from both sides.

−13y+5−5=18−5

−13y=13

Step 4: Divide both sides by -13.

−13y

−13

=

13

−13

y=−1

Answer: y =-1

User Emii
by
5.9k points